2020
DOI: 10.1186/s12889-019-8045-x
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and the oral health of a nationally representative sample of Hispanic children in the United States: an analysis of 2011–2012 National Survey of Children’s Health data

Abstract: Background: Oral disease is a serious public health issue, and Hispanic children in the United States (US) are more likely than children of other racial/ethnic groups to experience dental caries. Although Hispanic children are a growing segment of the US population there is limited research on the association between acculturation and oral health outcomes in this population. This study examined the associations between household acculturation and pediatric oral health in the Hispanic population using a nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Surveys resembling the Japanese national statistics used in this study include the Organization for Economic Cooperation and Development Health Statistics [ 17 ] and the 2011–2012 National Survey of Children’s Health [ 18 ] carried out by the United States government. Surveys other than national statistics include a study of myopia among children in Taiwan by Shao-En Chan et al [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys resembling the Japanese national statistics used in this study include the Organization for Economic Cooperation and Development Health Statistics [ 17 ] and the 2011–2012 National Survey of Children’s Health [ 18 ] carried out by the United States government. Surveys other than national statistics include a study of myopia among children in Taiwan by Shao-En Chan et al [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few oral health outcomes, such as those associated with oral health behaviors including oral hygiene, dental visits and dental service utilization, have been studied in relation to the level of parental acculturation [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In a cross-sectional study that used language as a proxy measure of acculturation, more acculturated or English-speaking Latino mothers had a higher inclination to use dental services for the prevention of dental caries and reported higher self-efficacy related to taking their children for preventive visits and maintaining their child’s oral hygiene [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted with Latino mothers, the level of acculturation measured by length of stay in the USA was one of strongest predictors of high caries prevalence in children [ 14 ]. A study that analyzed household acculturation using the measure of language and parent nativity from the National Survey of Children’s Health concluded that, as the level of acculturation increased in the household, Latino children’s oral health also improved [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study on immigrant population concentrated on associations between household acculturation and dental caries experience. 9 Another study reported on the utility of theorybased factors associated with seeking preventive dental care in a sample of Mexican American adults. 10 Rota et al reported on oral health practices, beliefs, and dental service utilization of Albanian immigrants in Milwaukee, Wisconsin.…”
Section: Introductionmentioning
confidence: 99%